EDMODO-BASED BLENDED LEARNING MODEL ON NEWS TEXT MATERIALS FOR CLASS VIII - Fitri, Tifani Nurul; Diana, Purwati Zisca (ppjbsip, 2021)
This study and development are motivated by the use of internet-based technology that has not beenÂ maximized in learning in schools, especially junior high schools. Therefore, the purpose of this study is toÂ develop a learning model that combines the learning proces directly throught face-to-face online learningÂ through applications, so that researchers develop a blended learning model based on edmodo in learningÂ news text for class VIII SMP. This study uses the research and development (R & D) method, with the ADDIEÂ model development procedure, namely the analysis, design, development, implementation, and evaluationÂ steps. The results of this study indicate that the learning model that has been developed can be categorized asÂ